Genome sequence resources for three strains of the genus Clonostachys - Zongping Sun; Fan Zhang; Nana Zhong; Kang Zhou; Jun Tang (BMC Genomic Data)
Abstract Objective Clonostachys, a genus with rich morphological and ecological diversity in Bionectriaceae, has a wide distribution among diverse habitats. Several studies have reported Clonostachys fungi as effective biological agents against multiple fungal plant pathogens. To clarify the diversity and biocontrol mechanisms of the Clonostachys fungi, this study was undertaken to sequence and assemble the genomes of two C. chloroleuca and one C. rhizophaga. Data description Here, we performed genomic sequencing of three strains of genus Clonostachys collected from the China General Microbiological Culture Collection Center (CGMCC) using Illumina HiSeq 2500 sequencing technology. Whole genome analysis indicated that their genomes consist of 58,484,224 bp with a GC content of 48.58%, 58,114,960 bp with a GC content of 47.74% and 58,450,453 bp with a GC content of 48.58%, respectively. BUSCO analysis of the genome assembly indicated that the completeness of these genomes was at least 98%. In summary, these datasets provide a valuable resource for ongoing studies that include further exploration of biological function, marker development, enhanced biological control ability of Clonostachys fungi, and population diversity.